Scope and Limits of “Inclusivism” in Modern South Asia: Questioning Tagore’s and Agyeya’s “Universalism ” - Nicola Pozza (Ksiegarnia Akademicka Publishing, 2021)
During the twentieth century, it had become increasingly common among scholars working on modern India to oppose Indian leaders and authors advocating the idea of multicultural and secular India to those promoting a nation based solely on the so‑called “Hindu way of life.” While the discourse attributed to the former category has regularly been qualified as “universalist,” “inclusivist” or “tolerant,” the kind of nationalism fostered by the latter has variously been called “communalist” or “exclusivist.” While these antagonistic positions might certainly fit with the positions of iconic and emblematic figures such as M.K. Gandhi or V.D. Sawarkar respectively, they might well be misleading and too restrictive when applied to the discourses of authors such as Rabindranath Tagore (1861‑1941) and S.H. Vatsyayan ‘Agyeya’ (1911‑1987), to take into consideration only two among the most influential and celebrated authors and poets of modern India. Based on the analysis of Tagore’s and Agyeya’s texts, this contribution questions the accuracy of such a dichotomist categorization and more specifically the assertion that the works of twentieth‑century authors considered as “universalists” were actually presenting a picture of a united India with both Hindus and Muslims looking forward to a peaceful future together (Cush and Robinson, see footnote 3). It shows that, notwithstanding the real cosmopolitan worldview of both these authors, the Muslim realm is almost completely absent from their works. In conclusion, it is argued that far from being an exception, the position of these writers is illustrative of what can be called a “non‑exclusive Hindu nationalism,” which was pervasive among the Indian intellectuals of the twentieth‑century India.